Implementasi Kebijakan Inovasi Pojok Toboali (SIPOLI) dalam Perspektif Hukum Administrasi Daerah: Analisis terhadap Pemberdayaan Pelaku IKM di Kabupaten Bangka Selatan - Deka Indra (Fakultas Hukum Universitas Bangka Belitung, 2025)
This article analyses the implementation of the Toboali Corner Innovation Policy (SIPOLI) from the perspective of regional administrative law and its implications for empowering small and medium industries (IKM) in South Bangka Regency. Using a descriptive qualitative approach with a juridical–empirical design, the study combines normative analysis of regional regulatory frameworks particularly the Regent’s Decree of South Bangka Regency Number 188.45/29.C/DKUKMINDAG/2023 regarding the establishment of the Seafood Processing Industry Centre based on One Village One Product (OVOP) with field data obtained from in-depth interviews with 12 IKM actors, direct observation, and documentation. The findings show that SIPOLI constitutes a form of local government policy innovation within the framework of regional autonomy as mandated by Law Number 23 of 2014 on Regional Government and Law Number 20 of 2008 on Micro, Small, and Medium Enterprises. Substantively, SIPOLI fulfils the elements of distributive and facilitative policies aimed at empowering IKM through market access expansion, promotion, and product branding by placing local products in prominent souvenir outlets in Pangkalpinang City. Empirically, most IKM participants experienced an increase in sales of around 15–25% in the first three months after joining SIPOLI, alongside broader market exposure beyond the local area. However, from a regional administrative law perspective, the implementation of SIPOLI still faces several challenges, such as limited production capacity, incomplete fulfilment of product legality (home industry licence, halal certification, BPOM), uneven digital marketing capabilities, and the absence of more varied and sustainable promotional channels. These weaknesses indicate that legal and institutional support for IKM empowerment needs to be strengthened, both through regulatory refinement and continuous capacity-building.